Viscoelastic response of fluid trapped between two dissimilar van der Waals surfaces. (11th May 2022) - Tendong, E; Saha-Dasgupta, T; Chakrabarti, J
Abstract: Employing grand canonical Monte-Carlo and molecular dynamics simulations, the viscoelastic response of trapped fluid under molecularly thin confinement by walls having different wall–fluid interaction strengths, is investigated. With increase in slit asymmetry, given by the ratio of interaction strengths of the wall having strong wall–fluid interaction to that of the wall with weak wall–fluid interaction, a crossover in effective density of the fluid film, from rarer (R) to denser (D) than the bulk density is observed. Upon increasing asymmetry further, the dense fluid (F) layers undergo bond-orientational (S) ordering. The variation of viscoelastic relaxation time with scaled asymmetry shows a universal behavior, independent of slit width, with two distinct regimes. Below a critical value of asymmetry, the viscoelastic relaxation time is a slowly varying function of asymmetry, comparable with the structural relaxation time. Beyond the critical asymmetry, on the other hand, viscoelastic response time shows a sharp increase upon increasing asymmetry, deviating markedly from the structural relaxation time. Interestingly the critical asymmetry value is found to correlate with R to D crossover. The microscopic origin of the two-regime universal behavior of viscoelastic response time is found to stem from the fact that below critical asymmetry, the overall viscoelastic behaviour of the slit is dominated by that of the fast relaxing layer close to the weakly attracting surface, while above the critical asymmetry, the relaxation behaviour is guided by the dense fluid layer adjacent to the strongly attracting wall. In vicinity of fluid to ordering transition, the loss and storage moduli merge for low frequencies as in gel-like mechanical behaviour. The storage modulus takes over the loss modulus in the phase co-existence region even before the long ranged order sets in. Our findings bear important implications for fluid transport in hetero-structured geometry in nanotechnology.